Method of training female university students to meet the gto standards – level vii for spinal mobility - Kraynik, V.L. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to substantiate and develop a methodology for preparing university students to meet the GTO VI standards for determining the level of spinal mobility (forward bend from a standing position) and to recommend it for practical use. Methods and structure of the study. The experimental study was conducted at Altai State Pedagogical University in 2024 among first-year female students. The sample size was 50 people. To ensure the correct conduct of the experimental study, the following methods were selected: analysis of scientific and methodological literature, surveys, questionnaires, testing of baseline indicators of spinal mobility in female students, pedagogical observation, abstraction, systematization, modeling, methods of mathematical statistics, etc. Results and conclusions. At the preliminary stage of the study, the mobility of the spinal column of first-year female students was tested. A corrective technique for developing the mobility of the spinal column of female university students was developed, including 4 weekly cycles with exercises of increasing complexity to develop spinal flexibility.